In vivo knockdown of GAD67 in the amygdala disrupts fear extinction and the anxiolytic-like effect of diazepam in mice - Heldt, S A (Nature Publishing Group, 2012)
In mammals, γ-aminobutyric acid (GABA) transmission in the amygdala is particularly important for controlling levels of fear and anxiety. Most GABA synthesis in the brain is catalyzed in inhibitory neurons from ℒ-glutamic acid by the enzyme glutamic acid decarboxylase 67 (GAD67). In the current study, we sought to examine the acquisition and extinction of conditioned fear in mice with knocked down expression of the GABA synthesizing enzyme GAD67 in the amygdala using a lentiviral-based (LV) RNA interference strategy to locally induce loss-of-function. In vitro experiments revealed that our LV-siRNA-GAD67 construct diminished the expression of GAD67 as determined with western blot and fluorescent immunocytochemical analyses. In vivo experiments, in which male C57BL/6J mice received bilateral amygdala microinjections, revealed that LV-siRNA-GAD67 injections produce significant inhibition of endogenous GAD67 when compared with control injections. In contrast, no significant changes in GAD65 expression were detected in the amygdala, validating the specificity of LV knockdown. Behavioral experiments showed that LV knockdown of GAD67 results in a deficit in the extinction, but not the acquisition or retention, of fear as measured by conditioned freezing. GAD67 knockdown did not affect baseline locomotion or basal measures of anxiety as measured in open field apparatus. However, diminished GAD67 in the amygdala blunted the anxiolytic-like effect of diazepam (1.5 mg kg(–1)) as measured in the elevated plus maze. Together, these studies suggest that of GABAergic transmission in amygdala mediates the inhibition of conditioned fear and the anxiolytic-like effect of diazepam in adult mice.